2017
DOI: 10.1007/s00268-017-3928-4
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Laparoscopic Cholecystectomy for Acute Calculous Cholecystitis: Is it Time for a Change?

Abstract: Delayed LC is associated with significant loss of follow-up, long LOS, and higher than expected use of PC. Conversion rates are lower than in the literature while rates of bile duct injury and mortality are comparable. We believe these data as well as the available literature are sufficient to change our hospital policy regarding the surgical treatment of ACC from delayed to early same admission surgery in appropriate cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
5
0
3
Order By: Relevance
“…Figure 1 shows the modified PRISMA flowchart for identification and inclusion of relevant papers. Twentythree studies were excluded from the meta-analysis; 10 papers were deemed low quality [53][54][55][56][57][58][59][60][61] and 13 papers did not provide readmission rates specific to LC [62][63][64][65][66][67][68][69][70][71][72][73][74].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the modified PRISMA flowchart for identification and inclusion of relevant papers. Twentythree studies were excluded from the meta-analysis; 10 papers were deemed low quality [53][54][55][56][57][58][59][60][61] and 13 papers did not provide readmission rates specific to LC [62][63][64][65][66][67][68][69][70][71][72][73][74].…”
Section: Resultsmentioning
confidence: 99%
“…In cholecystitis without septic shock, 30-day mortality has been reported to be between 0.6% and 1.1%. 18,19 In patients with acute cholecystitis with associated organ dysfunction, Yokoe and colleagues reported in a multicentre study that mortality ranged from 3.1% to 25% depending on the number of organ failures present. 20 Anderson and colleagues reported in a multicentre database study of patients with acalculous cholecystitis that sepsis had a hazard ratio (HR) of 1.72 and shock had an HR of 2.07 for mortality.…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…10 A recent study from Israel shows a conversion rate of 5.8%. 11 In another study by Kumar et.al from Utarpardesh India shows a conversion rate of 4.5% 12 and another study from Palpa, Nepal shows a conversion rate of 6.9%. 13 When we compared our conversion rate to the local and international literature we found that our conversion rate was far less than the local and international eviedence available.…”
Section: Discussionmentioning
confidence: 89%